2002
DOI: 10.1207/s15374424jccp3103_08
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Anxious Parents: Examining Mechanisms of Transmission of Anxiety From Parent to Child

Abstract: Examined the behavior of anxious parents in interactions with their children (ages 6 to 12 years) to test hypotheses about possible psychosocial mechanisms of transmission of anxiety from parent to child. Fifty-one parent-child dyads completed the study. Parents and children were assessed with structured interviews and participated in 2 tasks that were videotaped and coded. Twenty-five dyads had an anxious parent. Primary diagnoses of the anxious group were mostly panic disorder (PD), with or without agoraphob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 240 publications
(80 citation statements)
references
References 41 publications
6
71
1
2
Order By: Relevance
“…This supposition is again supported by the work of Rutherford (2003) and Woodruff-Borden et al (2002) who both suggested that having a parent model acceptance of both negative and positive emotions rather than just the latter is an important demonstration for children to develop their own methods of coping and management. Both of these sets of researchers found that anxious mothers were less comfortable with their children's negative emotion and so were more intent on stopping them than assisting the children with working through them.…”
Section: Significance Of the Stress Management Scale The Stress Manamentioning
confidence: 85%
See 4 more Smart Citations
“…This supposition is again supported by the work of Rutherford (2003) and Woodruff-Borden et al (2002) who both suggested that having a parent model acceptance of both negative and positive emotions rather than just the latter is an important demonstration for children to develop their own methods of coping and management. Both of these sets of researchers found that anxious mothers were less comfortable with their children's negative emotion and so were more intent on stopping them than assisting the children with working through them.…”
Section: Significance Of the Stress Management Scale The Stress Manamentioning
confidence: 85%
“…through genetics (see Barlow, 2002); the reinforcement of anxious behaviours through parenting practices, whether done purposely or inadvertently (Fonagy, 2001;Hart, 2011;Hughes, 2009;Woodruff-Borden, Morrow, Bourland, & Cambron, 2002); and the modelling of anxious behaviours (Saarni, 1999). Each of these factors has the potential to influence a child's emotional development.…”
Section: Effects Of Parental Anxietymentioning
confidence: 99%
See 3 more Smart Citations